Effects of Gait Speed and Sole Adjustment on Shoe–Floor Angles: Measurement Using Shoe-Type Sensor - Yu Hashiguchi; Tsuguru Numabe; Ryosuke Goto (Biomechanics, 2024)
Background: Assessment of walking with shoes is important for understanding different types of walking in various environments. Methods: In this study, a shoe-type sensor was used to demonstrate the shoe–floor angle in fifteen participants who walked on a treadmill under varying gait speed and sole adjustments, lifting one side of the sole. The shoe–floor angle in the sagittal; the angle of toe-up (θTup) and toe-down (θTdown) and frontal planes; and the angle of pronation (θPro) and supination (θSup) were calculated, and angles at the initial contact and maximum angles were extracted. Results: The results showed that most angles significantly increased with an increase in the gait speed (θTup and θTdown; p < 0.01 both, θPro and θSup; p < 0.02 and 0.04). Conversely, only the supination angle at the initial contact changed significantly, owing to the tilt of the sole (p < 0.01). Conclusion: Shoe movements were more strongly affected by gait speed than by sole adjustment.